Solidity in a Turbulent Flow: The Social Network of Aristocratic Families in the Eastern Jin Dynasty (317–420 C.E.) - Wenyi Shang; Zizhou Sang (Journal of Historical Network Research, 2021)
Historians characterized the Eastern Jin (317–420 C.E.) as an era dominated by aristocratic families. Network analysis provides a unique perspective to understanding these families by expanding the scope of research from imperial politics to the aristocrats’ social world. This article reconstructs the aristocratic social network from A New Account of the Tales of the World (Shishuo xinyu 世說新語), a collection of anecdotes that provides rich information on the aristocrats’ social interactions in this period, and provides a comprehensive analysis of the network. This article uses network simulation and Exponential Random Graph Models (ERGM) to describe the structure of this network. It calculates cumulative edge weights to measure the homophily by family affiliation in the network and computes several centrality measures to evaluate the importance of various historical figures. These results demonstrate that homophily by family affiliation exists in this network but is weak. Although members of the same family are prone to have close ties, social relationships across aristocratic families were also common. In contrast to many existing studies that emphasize the conflicts between aristocratic families, this article argues that there was a notable degree of social cohesion that united the aristocratic families as a status group during the Eastern Jin. This cohesion provides an element of solidity in the turbulent flow of their political fortunes, which was one of the main reasons why these aristocratic families as a privileged status group successfully dominated politics and social life throughout the century of the Eastern Jin.